Surveillance of Device-Associated Infections in Critical Patient Care Areas - Khan, Mumtaz Ahmed (International Journal of Pathology, 2018)
Objectives: To determine Device-associated infections (DA-HAIs) rates, microbiological profiles and resistancepatterns of infecting organisms in intensive care units and step down unit of a tertiary care hospital in Saudi Arabia.Study Design: Prospective descriptive study.Place and duration of study: The study was carried out at King Abdullah Hospital Bisha, Kingdom of SaudiArabia over a period of 12 months from January to December 2011.Materials and Methods: A prospective, active DA-HAI surveillance study was conducted in criticalcare patientareas from Jan 2011 to Dec 2011. The rates of ventilator-associated pneumonia (VAP), central catheter-associatedbloodstream infection (CLABSI), and catheter-associated urinary tract infection (CAUTI) were calculated alongwith microbiological profile, and antimicrobial resistance.Results: Surveillance data was obtained by trained infection control professionals using standard CDC criteria forHAIs.From January through December 2011, a total of 129 DA-HAIs were reported: 74 (57.36%) were cases of VAP, 34(26.35%) were cases of CAUTI, and 21 (16.29%) were cases of CLABSI.Conclusion: Increase rates of DAIs emphasize the need to improve infection control practices and management ofinvasive device in hospital. In critical patient areas, ongoing surveillance programs and implementation of qualityimprovement projects could contribute to reducing HAIs.